A Technocratic Way? Elite-led Democratic Innovations Within Conservative Parties - Gema Sánchez Medero; F. Ramón Villaplana (Acta Politologica)
In recent years, studies on democratic innovations within political parties have proliferated, driven by the success of new digital parties. However, there remains a gap in the literature regarding such innovations in mainstream and conservative parties, and particularly about the motivations behind their implementation (or lack thereof). This article uses as example the case of the Spanish People’s Party (Partido Popular or PP), one of the largest conservative parties in Europe with over 45 years of history. We identify the key organizational innovations introduced by the PP in the last decade and evaluate the impact of its digitalization on intra-party democracy. Our preliminary analysis suggests that the democratic innovations implemented by the PP, including party primaries at the national level for first time in 2018, mostly reflect a technocratic approach to organizational updating, characterized by elite-controlled democratization and uneven digitalization efforts, primarily focused on social media and communication purposes, with the absence of any e-voting mechanism. These findings, along with previous literature on the topic, suggest a recurring pattern in how conservative parties deal with their own democratization and adapt to the digital age.